Atopic Dermatitis as a Risk Factor of Herpes Simplex Virus Type 1 Reactivation: a Case Report - Putri, Andi A. M.; Soegyanto, Anandina I. (Hasanuddin University, 2020)
Objective: Atopic Dermatitis (AD) is a recurrent chronic inflammatory skin disease that causes skin barrier defects and improper immunologic responses. This disease has high possibility to develop infections and reactivation of latent viruses, such as HSV-1 reactivation. This case report will review the potency of AD as a risk factor of orofacial HSV-1 reactivation.Method: A 43 years-old female came to Universitas Indonesia dental hospital with painful mouth ulcers. She felt weak, dizzy, and feverish for a week, with history of allergies which also runs in her family. Clinical examination showed multiple erosion on her face, hands, and legs; crust on the right lower vermillion border; multiple ulcers on the lower labial, right buccal and palate mucosa, with erythema on the anterior tongue. The patient was diagnosed with recurrent orofacial herpes and treated with topical acyclovir 5% cream, chlorhexidine gluconate 0.2% mouthrinse, and a multivitamin. Her skin lesion has been discussed with a dermatologist and diagnosed as AD.Results: A week after therapy, all oral lesion was improved and totally disappeared after several weeks. Atopic dermatitis is a recurrent chronic inflammatory skin disease that can significantly affect the quality of life. Therefore, the skin barrier defect and the decrease of immune systems contribute to the increased susceptibility to recurrent HSV infections.Conclusion: Atopic dermatitis may be a risk factor for HSV-1 reactivation, including recurrent orofacial herpes.